The higher education access experiences of African disadvantaged students - Makhanya, T. B. (South African Journal of Higher Education, 2024)
The institutions of higher learning in South Africa (HEIs) still suffer from the remains of colonialism. Many different activities in HEI have exposed such legacy. For instance, the 2015/2016 #fees must fall, and Rhodes must fall mass student’s protest exposed struggle for transformation in academic institutions. The current article wants to understand participants (which are graduates) experiences with regards to accessing the university. Twenty-two graduates were interviewed through individual semi-structured interviews. In a setting that still suffer from legacies of oppression, participants emphasised absence of easy access at the university as symbolising the still existing European domination in African institutions. Thus, poor students access experiences at the university are marked by misperceptions and disappointments due to several obstacles. There is a need for fundamental change in HEIs, by making certain that an inclusive admission of poor students in post-colonial South African universities is evident.